Implementation Of The Positive Culture Of Seven Days Of Special Education At SDN 1 Pasanggrahan - Nurhayati, Tita; Retnoasih, Agustina; Purwanto; Halimah, Lili (Universitas Negeri Semarang, 2024)
Education is the place where the seeds of culture are sown within society. Through the educational process, good character traits develop within individuals, equipping them to face life with physical and spiritual happiness. Education is a place for character formation. A positive culture involves good habits encompassing activities fostering students' character. The Government of Purwakarta Regency issued Regent Regulation Number 69 of 2015 on Education, laden with Sundanese philosophy through the